Geological Structures a Practical Introduction - Waldron, John; Snyder, Morgan (Open textbook library., 2020)
This manual is about structures that occur within the Earth’s crust. Structures are the features that allow geologists to figure out how parts of the Earth have changed position, orientation, size and shape over time. This work requires careful observation and measurements of features at the surface of the Earth, and deductions about what’s below the surface. The practical skills you will learn in this course form the foundation for much of what is known about the history of the Earth, and are important tools for exploring the subsurface. They are essential for Earth scientists of all kinds. The course that this document supports is about doing structural geology. It’s not possible to be a good geologist (or to pass the course) just by learning facts. You have to be able to solve problems. Do your lab work conscientiously and get as much as possible done during lab sessions when instructors are available to help you. This manual consists of both readings and lab exercises, which alternate through the text. The readings are designed to be read and understood outside the lab sessions, whereas the labs contain specific instructions and questions to be completed. Before each lab, be sure you have covered the readings that come immediately before it.